Antioxidant and pancreatic lipase inhibitory effects of flavonoids from different citrus peel extracts: An in vitro study. (1st October 2020) - Huang, Rui; Zhang, Yu; Shen, Shuyu; Zhi, Zijian; Cheng, Huan; Chen, Shiguo; Ye, Xingqian
Highlights: Ponkan peel extract is a promising natural ingredient to scavenge free radicals and manage obesity. Hesperidin was found to be the potential pancreatic lipase inhibitor. Hydrogen bonds and van der Waals forces were the main driving forces in the interaction. Secondary structure of pancreatic lipase was not obviously changed by the interaction with hesperidin. Abstract: Obesity and oxidative damage are two important risk factors associated closely with metabolic syndrome. Utilization of functional food ingredients is considered as a feasible way to tackle these challenges. In the present study, eight representative species of citrus peel extracts (CPEs) were evaluated and compared for their flavonoid profiles, antioxidant activities, and pancreatic lipase (PL) inhibitory capacities and mechanisms. Results indicated that hesperidin, naringin, neohesperidin, narirutin and eriocitrin were the five major flavonoids in CPEs, among which hesperidin was the main active PL inhibitor. Moreover, hesperidin could interact with PL by hydrogen bonds and van der Waals forces, and the interaction would not obviously change the secondary structure of PL. Overall, ponkan peel extract, having the strongest overall antioxidant activity, the highest content of hesperidin and total phenolic compounds among all tested CPEs, is a promising natural ingredient to scavenge free radicals and manage obesity.